2009
DOI: 10.1111/j.1600-0838.2008.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and quality of life in schoolchildren aged 11–13 years of Cuenca, Spain

Abstract: This study examined the differences in quality of life (QoL) between active and sedentary schoolchildren and analyzed these differences by gender and weight status. A total of 1409 children, aged 11-13 years, from 20 schools located in 20 municipalities of the province of Cuenca were invited to participate in a cross-sectional study; 1073 children agreed (76.15% response rate), of which 536 (49.9%) were boys. QoL was measured with Child Health and Illness Profile-Child Edition (CHIP-CE), an instrument measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
4
33
1
5
Order By: Relevance
“…More active children report better HRQL than sedentary children [12]; however, a previous study found that weekly PA hours at the age of 15-16 were only weakly associated with mental health just 3 years later in boys, and no association for girls [11]. In adults, studies have reported significant positive associations between current PA and most SF-36 domains in healthy general populations for both genders and across all age groups [45][46][47][48], indicating the importance of regular PA for HRQL as well as for objective health measures and disease prevention [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…More active children report better HRQL than sedentary children [12]; however, a previous study found that weekly PA hours at the age of 15-16 were only weakly associated with mental health just 3 years later in boys, and no association for girls [11]. In adults, studies have reported significant positive associations between current PA and most SF-36 domains in healthy general populations for both genders and across all age groups [45][46][47][48], indicating the importance of regular PA for HRQL as well as for objective health measures and disease prevention [48].…”
Section: Discussionmentioning
confidence: 98%
“…A large US general population survey found that obese adults were significantly more likely than normal weight adults to have experienced [14 unhealthy days (physical or mental), or [14 days with activity limitations, over the past month [8], and adults meeting public health recommendations for PA were significantly less likely to report C14 unhealthy days compared to inactive adults [9], illustrating the public health impact in terms of adult productivity. More limited research also exists linking youth obesity to poorer youth HRQL, and youth PA to better youth HRQL, including effects on self-reported health, as well as physical, emotional, and social health and functioning [10][11][12][13][14]. However, not all research is consistent: in particular, some studies in adults have shown a positive association between adult obesity and mental HRQL [15][16][17].…”
Section: Introductionmentioning
confidence: 90%
“…9 Physical inactivity 10 and obesity 11 have been documented as important correlates of low HRQoL in adults. The association between physical activity and sedentary behavior with HRQoL among adolescents is not sufficiently established, 12 although previous studies have documented that the highest level of physical activity and a lower level of screen-based media use are associated with highest level of HRQoL. 13,14 By contrast, Boyle et al 15 found that there were no differences in HRQoL when active adolescents were compared with inactive ones.…”
Section: Introductionmentioning
confidence: 92%
“…This concept of sport has been used previously by other authors who indicate that the term ''sport'' can cover different forms of physical activity (Kirkcaldy, Shephard, & Siefen, 2002). Participation in sport activities can be related to different aspects of mental health such as dimensions of psychological well-being (Kirkcaldy et al, 2002;Ussher, Owen, Cook, & Whincup, 2007;Biddle & Mutrie, 2008, Sánchez-López et al, 2009, prevalence of mental disorders, including depression and anxiety disorders (Kirkcaldy et al, 2002;Desha, Ziviani, Nicholson, Martin, & Darnell, 2007;Ströhle, 2009;Skrove et al, 2013;Moljord et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…In the current research, participation in sport activities was measured not as a single dimension, i.e., the frequency of physical activity, as was the case in some of the aforementioned investigations, but as a complex measure that consistently incorporates intensity, frequency and duration of sport activities (for more information, see section ''Measures''). It has been established that participation in physical activities can be analyzed in relation to the different extents of participation, otherwise called categories (see Booth, Okely, Chey, & Bauman, 2001;Sánchez-López et al, 2009;Tao et al, 2007;Wiles et al, 2008). The recommendations of other authors were taken into consideration (Sallis & Patrick, 1994;Booth et al, 2001), and the scheme of five categories of participation in sport activities was formulated.…”
Section: Introductionmentioning
confidence: 99%